Research on The Value Realization of Ecological Products - Shi, Yanlong (International Journal of Management and Education in Human Development, 2023)
With the development of economic globalization, ecological problems are not only a development problem of a country, but also an important problem facing all countries in the world. Ecological issues not only involve environmental protection, but also involve economic, social, political and other comprehensive issues. To properly handle the relationship between human beings and ecology will contribute to the long-term stability of the society and the country. Therefore, this paper analyzes the problems faced by the ecological product value, and on this basis, puts forward the ecological product value realization way, mainly including the establishment of ecological product value realization system, speed up the construction of ecological product value realization market trading system, improve the relevant legal mechanism, improve the guarantee mechanism of ecological products and so on four aspects. In order to promote the value of ecological products, accelerate the promotion of national, and even global ecological civilization construction.